Deciphering the quenching mechanism of 2D MnO2 nanosheets towards Au nanocluster fluorescence to design effective glutathione biosensors. Issue 19 (28th April 2016) - Lin, Shichao; Cheng, Hanjun; Ouyang, Qiran; Wei, Hui
Abstract : A turn-on fluorescent platform was developed for glutathione detection by recovering the MnO2 nanosheet quenched fluorescence of gold nanoclusters. Abstract : Two-dimensional (2D) nanomaterials (such as 2D MnO2 nanosheets) have received increasing attention due to their unique photophysical properties, rich redox chemistry, excellent colloidal stability, good biocompatibility, etc. Recently, numerous sensing platforms have been reported by exploring the 2D MnO2 nanosheet mediated fluorescence quenching towards fluorophores and/or redox reactions between MnO2 and reductive targets. Though various fluorophores have been used in 2D MnO2 nanosheet based turn-on sensing systems, ultrasmall metal nanoclusters have not been exploited yet. Furthermore, the quenching mechanisms of MnO2 nanosheets towards various fluorophores have remained elusive. To address these issues, we studied the quenching of Au nanocluster fluorescence by 2D MnO2 nanosheets. First, we demonstrated that 2D MnO2 nanosheets were effective quenchers towards the fluorescence of metal nanoclusters ( e.g., AuNC@BSA, the bovine serum albumin stabilized Au nanocluster). We further revealed that both dynamic and static quenching effects played critical roles in the quenching process while fluorescence resonance energy transfer (FRET) and inner filter effect (IFE) only played very minor roles in the quenching process. Finally, we developed a turn-on sensing strategy for detection of glutathione (GSH), an important antioxidant with good sensitivity and selectivity. This work provides useful insights in understanding the mechanisms of nanomaterial-induced fluorescence quenching. It also paves a way to design turn-on fluorescent sensors for important reductive targets.